1999
DOI: 10.1121/1.428217
|View full text |Cite
|
Sign up to set email alerts
|

Training American listeners to perceive Mandarin tones

Abstract: Auditory training has been shown to be effective in the identification of non-native segmental distinctions. In this study, it was investigated whether such training is applicable to the acquisition of non-native suprasegmental contrasts, i.e., Mandarin tones. Using the high-variability paradigm, eight American learners of Mandarin were trained in eight sessions during the course of two weeks to identify the four tones in natural words produced by native Mandarin talkers. The trainees' identification accuracy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

39
318
6
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 372 publications
(365 citation statements)
references
References 19 publications
39
318
6
2
Order By: Relevance
“…Infants learning Chinese show preferences for the tonal contrasts of their native language by about 4-5 mo of age (18), well in advance of the age of adoption (AoA) of participants in the present study. In addition, learning to perceive these tonal contrasts as distinct linguistic categories is difficult for adults without prior experience with tone languages (21). This suggests that receiving early input in this domain is crucial for later discrimination of tonal categories.…”
mentioning
confidence: 99%
“…Infants learning Chinese show preferences for the tonal contrasts of their native language by about 4-5 mo of age (18), well in advance of the age of adoption (AoA) of participants in the present study. In addition, learning to perceive these tonal contrasts as distinct linguistic categories is difficult for adults without prior experience with tone languages (21). This suggests that receiving early input in this domain is crucial for later discrimination of tonal categories.…”
mentioning
confidence: 99%
“…This generalization does have its limits: When the listeners were tested on English sentences with a very different accent (Slovakian), there was no significant advantage for any of the training types of phonetic distinctions as well. Wang, Spence, Jongman, and Sereno (1999) applied Logan et al's (1991) high-variance training approach to native English speakers trying to learn Mandarin tones. In Mandarin, there are four different prosodic patterns that can be imposed on a syllable, and these four tones combine with the phonetic information to determine the lexical identity of the word.…”
Section: I2 Perceptual Learning Of Accents and Idiolectsmentioning
confidence: 99%
“…Training on suprasegmentals has lagged somewhat behind that of well-established phonemic segmental contrasts but work has been done in the areas of tone (So, 2006;Wang, Spence, Jongman, & Sereno, 1999) and stress (Archibald, 1992;Carpenter, 2006Carpenter, , 2010Yeung & Nazzi, 2014). Wang et al (1999) report on the training of American English listeners to perceive Mandarin tones more accurately. Adapting the high-variability, multi-talker paradigm developed for segmental training (Lively et al, 1993) to suprasegmental training, Wang et al (1999) found that learners of Mandarin tone were able to increase their overall tone perception accuracy by a significant 21%.…”
Section: Introductionmentioning
confidence: 99%
“…Segmental training has included the English /ð/ ~ /Ɵ/ contrast for French speakers (Jamieson & Morosan, 1986), and most notably, the English /l/ ~ /r/ contrast for Japanese speakers (Best, 1995;Iverson, Hazan, & Bannister, 2005;Lively, Logan, & Pisoni, 1993;Logan, Lively, & Pisoni, 1991;Strange & Dittman, 1984;Takagi, 2002). Training on suprasegmentals has lagged somewhat behind that of well-established phonemic segmental contrasts but work has been done in the areas of tone (So, 2006;Wang, Spence, Jongman, & Sereno, 1999) and stress (Archibald, 1992;Carpenter, 2006Carpenter, , 2010Yeung & Nazzi, 2014). Wang et al (1999) report on the training of American English listeners to perceive Mandarin tones more accurately.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation